2003
DOI: 10.5194/acp-3-2043-2003
|View full text |Cite
|
Sign up to set email alerts
|

DRIFTS and Knudsen cell study of the heterogeneous reactivity of SO<sub>2</sub> and NO<sub>2</sub> on mineral dust

Abstract: Abstract. The heterogeneous oxidation of SO 2 by NO 2 on mineral dust was studied using Diffuse Reflectance Infrared Fourier Transform Spectroscopy (DRIFTS) and a Knudsen cell. This made it possible to characterise, kinetically, both the formation of sulfate and nitrate as surface products and the gas phase loss of the reactive species. The gas phase loss rate was determined to be first order in both SO 2 and NO 2 . From the DRIFTS experiment the uptake coefficient, γ , for the formation of sulfate was determi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 38 publications
(55 reference statements)
4
112
1
Order By: Relevance
“…Therefore, accessible active sites also decreased with time. Previous research has found that γ obs depends on sample mass due to the diffusion of reactant gas into the underlying layers of the multilayer powder sample 2010b, c;Ullerstam et al, 2003;Underwood et al, 2000 and2001). Some studies have found, however, that uptake coefficient is unrelated to sample mass (Qiu et al, 2011;Seisel et al, 2005).…”
Section: Kinetics Of Ma Uptake Onto Ammonium Saltsmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, accessible active sites also decreased with time. Previous research has found that γ obs depends on sample mass due to the diffusion of reactant gas into the underlying layers of the multilayer powder sample 2010b, c;Ullerstam et al, 2003;Underwood et al, 2000 and2001). Some studies have found, however, that uptake coefficient is unrelated to sample mass (Qiu et al, 2011;Seisel et al, 2005).…”
Section: Kinetics Of Ma Uptake Onto Ammonium Saltsmentioning
confidence: 90%
“…Prior to the experiments, the reactor chamber was passivated with amines for 90 min until a steady state QMS signal was established as the samples were isolated from the gas by the sample cover. The observed uptake coefficients (γ obs ) were calculated with a Knudsen cell equation (Tabor et al, 1994;Ullerstam et al 2003;Underwood et al, 2000).…”
Section: Uptake Experimentsmentioning
confidence: 99%
“…26 For steady-state uptake, the uptake coefficient can be calculated using the Knudsen cell equation: [26][27][28][29] where A h is the effective area of the escape aperture (m 2 ), A s is the geometric area of the sample holder (m 2 ); I 0 and I are the mass spectral intensities with the sample holder closed and open, respectively. As for the multilayer powder sample, the linear mass dependent (LMD) region of the observed uptake coefficient has been reported by different groups in various reaction systems, and has been ascribed to the diffusion of reactant molecules into the underlying layers of multilayer powder samples.…”
Section: The Effect Of Temperature On the Heterogeneousmentioning
confidence: 99%
“…As for the multilayer powder sample, the linear mass dependent (LMD) region of the observed uptake coefficient has been reported by different groups in various reaction systems, and has been ascribed to the diffusion of reactant molecules into the underlying layers of multilayer powder samples. [29][30][31][32][33] Therefore, the true uptake coefficients, γ t , can be calculated from where "slope" is the slope of the plot of γ versus sample mass in the linear regime (kg -1 ), A s is the geometric area (m 2 ) of the sample holder, and S BET is the specific surface area of the particle sample (m 2 ‚kg -1 ). 34 As shown in Figure 3, there was a strong linear dependence of uptake coefficients at the initial time γ(Ini) and at steady state γ(SS) versus sample mass.…”
Section: The Effect Of Temperature On the Heterogeneousmentioning
confidence: 99%
“…[28][29][30][31][32][33][34] Diffuse reflectance infrared Fourier transform spectrometry (DRIFTS) is a powerful technique for following the chemistry of solid particles in real time under laboratory conditions. [35][36][37][38] It has the advantage of relatively strong signals due to the macroscopic amounts of sample used, but the matrix used must be infrared transparent. DRIFTS is not normally applicable to liquids where interface and bulk liquid phase reactions are important.…”
Section: Introductionmentioning
confidence: 99%